Coordination chemistry and biological activity of bidentate and quadridentate nitrogen–sulfur donor ligands and their complexes - H. Tarafder, M. Tofazzal; Ali, A. Manaf; Elias, M. Suhaimi; Crouse, Karen A.; Silong, Sidik (Springer, 2000)
The ligand S-benzyldithiocarbazate (SBDTC) acts as a bidentate sulfur-nitrogen chelating agent. The reaction of SnII or SbIII with SBDTC under alkaline conditions gives complexes of composition [Sn(SBDTCA)2]·2H2O and [Sb(SBDTCA)Cl2·2H2O]. A quadridentate Schiff base of SBDTC with benzil, having a donor sequence SNNS, yields complexes, [Cd(SNNS)] and [Zr(O)(SNNS)·H2O]. The ligands and the complexes have been characterized by elemental analyses, i.r., u.v.-vis., molar conductance measurements and 1H-n.m.r. spectroscopy. SBDTC, SnII and SbIII complexes and the SNNS Schiff base together with its CdII and ZrIV complexes display significant antifungal, antibacterial and anti-cancer activity. The SnII complex and the SNNS free Schiff base were very effective against Melanoma (skin cancer cells). The SBDTC and its SnII complex were also very effective against Renal carcinoma (kidney cancer cells). The results have been compared with those of the uncomplexed metal salts and the free ligands. The minimum concentrations for the evaluation of the above activities for CD50 of the samples were in the 1.0-15 μg cm-3 range.